2019
DOI: 10.1039/c9ta09482b
|View full text |Cite
|
Sign up to set email alerts
|

Cu–Fe–Ni nano alloy particles obtained by exsolution from Cu(Ni)Fe2O4 as active anode for SOFCs

Abstract: The metal exsolution of anodes was studied using spinel oxides of CuFe2O4 for enhancing the anodic activity of electrodes for solid oxide fuel cells (SOFCs) at lower temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Reports have also demonstrated the exsolution of alloys involving three metals, and examples include Fe−Ni−Ru from LnFe 0.7− x Ni 0.3 Ru x O 3‐δ (Ln=La, Pr) [36] and Re−Ni−Fe from LaNi 0.2 Re x Fe 0.6 O 3+δ –La 3 ReO 8 [37] both being highly active and stable for methane dry reforming. Spinel oxides Cu 1− x Ni x Fe 2 O 4 were totally reduced to form a structure of exsolved metallic nanoparticles on a metal matrix (e.g., Cu‐rich Cu−Ni−Fe alloys on a Fe‐rich Fe−Ni−Cu matrix from Cu 0.9 Ni 0.1 Fe 2 O 4 ) [38] . The material served as a highly active anode for electrochemical H 2 oxidation and demonstrated much smaller anodic polarization resistance than that of a conventional NiFe alloy anode, which was ascribed to the unique alloy structure [38] …”
Section: Multielement Nanostructured Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have also demonstrated the exsolution of alloys involving three metals, and examples include Fe−Ni−Ru from LnFe 0.7− x Ni 0.3 Ru x O 3‐δ (Ln=La, Pr) [36] and Re−Ni−Fe from LaNi 0.2 Re x Fe 0.6 O 3+δ –La 3 ReO 8 [37] both being highly active and stable for methane dry reforming. Spinel oxides Cu 1− x Ni x Fe 2 O 4 were totally reduced to form a structure of exsolved metallic nanoparticles on a metal matrix (e.g., Cu‐rich Cu−Ni−Fe alloys on a Fe‐rich Fe−Ni−Cu matrix from Cu 0.9 Ni 0.1 Fe 2 O 4 ) [38] . The material served as a highly active anode for electrochemical H 2 oxidation and demonstrated much smaller anodic polarization resistance than that of a conventional NiFe alloy anode, which was ascribed to the unique alloy structure [38] …”
Section: Multielement Nanostructured Systemsmentioning
confidence: 99%
“…Spinel oxides Cu 1− x Ni x Fe 2 O 4 were totally reduced to form a structure of exsolved metallic nanoparticles on a metal matrix (e.g., Cu‐rich Cu−Ni−Fe alloys on a Fe‐rich Fe−Ni−Cu matrix from Cu 0.9 Ni 0.1 Fe 2 O 4 ) [38] . The material served as a highly active anode for electrochemical H 2 oxidation and demonstrated much smaller anodic polarization resistance than that of a conventional NiFe alloy anode, which was ascribed to the unique alloy structure [38] …”
Section: Multielement Nanostructured Systemsmentioning
confidence: 99%
“…A recent study presented Cu−Fe−Ni exsolution in the form of nanosized Cu-rich and Fe-rich ternary alloys, exsolving from Cu 1−x Ni x Fe 2 O 4 spinels at 800 °C under wet H 2 , as a strategy to produce active SOFC anodes. 16 A ternary Co−Ni−Mo alloy was also used to impregnate a Sr 2 FeMoO 6−δ anode, 17 achieving lower electrode polarization resistance (R P ) values than impregnating with precious metals such as Pd. The results found in these studies suggest that ternary alloys can be interesting alternatives to improve the catalytic activity of SOFC's anodes.…”
mentioning
confidence: 99%
“…For the Cu1-xNixFe2O4 spinel oxide, Kang et al, reported the two different phases of ex-solved alloys: independent Cu-rich and Fe-rich ternary CuFeNi alloys during a reductive heat treatment. 82 Therefore, while finding the combination of elements to form alloy nanoparticles is pivotal to achieve the required properties demanded by specific applications, the conventional heuristic design may be a time-and resource-consuming task.…”
Section: Perspective On Future Research Directionsmentioning
confidence: 99%
“…So far, the experimentally confirmed ex-solved binary alloys are NiCu, 80,83 CuFe, 84 CoFe, 45,57,[85][86][87][88][89] CoNi, 10, 56, 90, 91 NiFe, 13,23,26,84,[92][93][94][95][96][97][98] Pt3Ni, 99 ReFe, 96 RhNi, 100 and RuFe, 101 and the ternary alloy are CuFeNi, 82 and ReNiFe 96 (Figure 12). Taking into account that possible candidates of metal ex-solutes are Fe, Co, Ni, Cu, Ru, Rh, Pd, Ag, Re, Ir, Pt, and Au, among others, combinations of two to construct a binary system will number more than 66 types, emphasizing the fact that only limited alloy compounds are confirmed empirically as of the present.…”
Section: Perspective On Future Research Directionsmentioning
confidence: 99%